Impact of radiation on host immune system in patients treated with chemoradiotherapy and durvalumab consolidation for unresectable locally advanced non-small cell lung cancer - Pasquier, Corentin; Chaltiel, Léonor; Massabeau, Carole; Rabeau, Audrey; Lebas, Louisiane; Lusque, Amélie; Texier, Jean-Sébastien; Moyal, Elizabeth Cohen-Jonathan; Mazières, Julien; Khalifa, Jonathan (Frontiers in Oncology, 2023)
Background: The optimal modalities of radiotherapy when combining concurrent chemoradiation (CCRT) and immunotherapy (IO) for locally advanced non-small cell lung cancer (LA-NSCLC) remain to be determined. The aim of this study was to investigate the impact of radiation to different immune structures and immune cells in patients treated by CCRT followed by durvalumab. Material and methods: Clinico-pathologic data, pre and post-treatment blood counts and dosimetric data were collected among patients treated by CCRT and consolidation durvalumab for LA-NSCLC. Patients were divided into two groups according to the inclusion (NILN-R+) or not (NILN-R-) of at least one non-involved tumor draining lymph node station (NITDLN) in the clinical target volume (CTV). Progression free survival (PFS) and overall survival (OS) were estimated by the Kaplan-Meier method. Results: Fifty patients were included with a median follow-up of 23.2 months (95%CI 18.3-35.2). 2-year PFS and 2-year OS were 52.2% (95%CI: 35.8-66.3) and 66.2% (95%CI 46,5-80,1), respectively. In univariable analysis, NILN-R+ (HR:2.60, p=0.028), estimated dose to immune cells (EDRIC) >6.3 Gy (HR:3.19, p=0.049) and lymphopenia ≤500/mm3 at IO initiation (HR:2.69, p=0.021) were correlated with poorer PFS; lymphopenia ≤500/mm3 was also associated with poorer OS (HR:3.46, p=0.024). In multivariable analysis, NILN-R+ was the strongest factor associated with PFS (HR:3.15, p=0.017). Conclusion: The inclusion of at least one NITDLN station within the CTV was an independent factor for poorer PFS in the context of CCRT and durvalumab for LA-NSCLC. The optimal sparing of immune structures might be of interest to achieve a better synergy between radiotherapy and immunotherapy in this indication.